Aplikasi Si Petarung Inovasi Kemudahan Investasi: Strategi Penurunan Pengangguran di Kabupaten Sragen - Novariani Indri Utami; M Sabandi (IAI Nasional Laa Roiba Bogor, 2025)
The Si Petarung application is a technology-based innovation developed by the Sragen Regency Government to increase investment and reduce unemployment. This application aims to simplify the spatial planning permit process and provide electronic access to information related to spatial utilization. By digitizing permit services, bureaucratic obstacles that often hinder investment can be minimized, thereby attracting more investors to Sragen Regency. This study analyzes the effectiveness of Si Petarung in supporting investment and its role in unemployment reduction strategies. Data from the Central Statistics Agency (BPS) shows that since the application's implementation, the open unemployment rate in Sragen Regency has decreased significantly, from 4.76% in 2021 to 3.53% in 2024. This indicates that the ease of investment through Si Petarung has had a positive impact on job creation and regional economic growth. This study analyzes the effectiveness of Si Petarung in supporting investment and its role in unemployment reduction strategies. Data from the Central Statistics Agency (BPS) shows that since the application's implementation, the open unemployment rate in Sragen Regency has decreased significantly, from 4.76% in 2021 to 3.53% in 2024. This indicates that the ease of investment through Si Petarung has had a positive impact on job creation and regional economic growth. In addition to providing benefits to large investors, this application also supports the development of Micro, Small, and Medium Enterprises (MSMEs) by providing legal certainty regarding their business spatial planning. The application's effectiveness can be further enhanced by expanding public outreach and updating the system to make it more accessible to various groups. Overall, the Si Petarung application serves as a model for innovative spatial planning permits that not only supports investment but also provides a strategic solution to address unemployment in Sragen Regency. With continuous evaluation and development, this application has the potential to become a national model for effective and efficient digital transformation of public services.